IMPLEMENTASI SISTEM INFORMASI AKADEMIK BERBASIS WEB MOBILE PADA SMA PGRI PAGELARAN - Nabih Prayoga, Raihan; Fauzi, Fauzi (YHMM PUBLISHING, 2025)
In the field of education, access to accurate and timely information is a crucial factor in supporting institutional development and academic effectiveness. Along with the rapid digital transformation, educational institutions are increasingly required to adopt computerized systems to improve the quality of academic services. However, many schools still rely on manual data processing methods or simple tools such as Microsoft Excel, which are prone to human error, data inconsistency, and inefficiency in data retrieval across departments. This study focuses on the design and implementation of a web mobile based Academic Information System at SMA PGRI Pagelaran, which previously managed academic data manually. The existing system caused delays, difficulties in data searching, and reduced effectiveness in academic administration. To address these challenges, a web-mobile academic information system was developed to support academic processes more efficiently. The research employed the Waterfall development method, consisting of requirement analysis, system design, implementation, testing, and maintenance. Data collection techniques included observation, interviews, questionnaires, and literature study. System modeling was designed using Unified Modeling Language (UML), including use case diagrams, activity diagrams, and class diagrams. The system was developed using PHP as the programming language and MySQL as the database. The resulting system enables efficient management and access to academic data such as student records, teacher data, grades, attendance, schedules, and school information through mobile devices, thereby improving operational efficiency, data accuracy, and information accessibility for stakeholders.